INNOVATIVE ECONOMY FUTURE PERSPECTIVE: THEORY AND PRACTICE - Ikram Abdullayevich Navruzov (Ecomind Press, 2025)
This article talks about the world innovation economy, and also analyzes the role of innovative projects in attracting investments, the demand for innovative production and services in business, as well as funds directed to science. The article presents the opinions and approaches of economists on the subject, and interprets the effectiveness as a result of bringing the innovative economy to a higher level.
Keywords: Innovations, investments, innovative projects, business, investment in innovative production, service, science, Global Innovation Index.